2006
DOI: 10.1111/j.1601-183x.2006.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of two new X‐linked quantitative trait loci controlling corpus callosum size in the mouse

Abstract: Corpus callosum (CC) size is a complex trait, characterized by a gradation of values within a normal range, as well as abnormalities that include a small or totally absent CC. Among inbred mouse strains with defects of the CC, BTBR T 1 tf/J (BTBR) mice have the most extreme phenotype; all animals show total absence of the CC and severe reduction of the hippocampal commissure (HC). In contrast, the BALB/cByJ (BALB) strain has a low frequency of small CC and consistently normal HC. Reciprocal F 1 crosses between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 18 publications
(24 reference statements)
3
23
0
Order By: Relevance
“…The cross of 129 and BTBR showed a maternal effect, where mice with a BTBR mother and 129 father had substantially more abnormalities than those with a 129 mother and BTBR father. This pattern supports an earlier finding of an X-linked gene in BTBR that contributes to corpus callosum defects (Kusek et al , 2007). The 129 x BTBR cross was less severely affected than strain 129, whereas the BTBR x 129 cross was more severely abnormal than strain 129.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The cross of 129 and BTBR showed a maternal effect, where mice with a BTBR mother and 129 father had substantially more abnormalities than those with a 129 mother and BTBR father. This pattern supports an earlier finding of an X-linked gene in BTBR that contributes to corpus callosum defects (Kusek et al , 2007). The 129 x BTBR cross was less severely affected than strain 129, whereas the BTBR x 129 cross was more severely abnormal than strain 129.…”
Section: Resultssupporting
confidence: 91%
“…The crosses of BTBR x 129 show a striking reciprocal difference that may arise from an X-linked gene. The same pattern of results was apparent in crosses of BTBR and BALB/cByJ in a previous study (Kusek et al , 2007). The present data for reciprocals of BALB x BTBR (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Since a number of studies have reported corpus callosum deficits in autistics [11,15,28,54], this corpus callosum deficit in the BTBR strain makes it even more fascinating for further study as a possible mouse model of autism. We have recently mapped the corpus callosum deficiency seen in the BTBR mouse to two quantitative trait loci on the X Chromosome [32]. It is not yet known whether the genes on the X Chromosome that underlie these loci are related to autism, however, ongoing research in our laboratory is addressing that issue.…”
Section: Discussionmentioning
confidence: 99%
“…The recent return of BTBR neuroanatomy to autism-related research focus was fueled by the development and popularization of neuroimaging techniques allowing for a more systematic overview of brain morphology aberrations. Until 2013 most information about aberrant brain connectivity in BTBR mice, including the striking complete agenesis of corpus callosum (aCC) and reduction in the hippocampal commissure, came from postmortem histological assessments (Bohlen et al 2012, Jones-Davis et al 2013, Kusek et al 2007, Wahlsten et al 2003). Similar, changes in the shape and localization of many brain structures, including the hippocampus and amygdala (Mercier et al 2012), and the formation of Probst bundles were recently confirmed using these neuroimaging techniques (Dodero et al 2013, Ellegood et al 2013, Fenlon et al 2015, Sforazzini et al 2016, Yang et al 2009).…”
Section: Neuroanatomy Of the Btbr Mouse: Impaired Axon Guidance Anmentioning
confidence: 99%